Mitigating measles outbreaks in West Africa post-Ebola. Issue 11 (2nd November 2015) - Truelove, Shaun A; Moss, William J; Lessler, Justin
Abstract : The Ebola outbreak in 2014–2015 devastated the populations, economies and healthcare systems of Guinea, Liberia and Sierra Leone. With this devastation comes the impending threat of outbreaks of other infectious diseases like measles. Strategies for mitigating these risks must include both prevention, through vaccination, and case detection and management, focused on surveillance, diagnosis and appropriate clinical care and case management. With the high transmissibility of measles virus, small-scale reactive vaccinations will be essential to extinguish focal outbreaks, while national vaccination campaigns are needed to guarantee vaccination coverage targets are reached in the long term. Rapid and multifaceted strategies should carefully navigate challenges present in the wake of Ebola, while also taking advantage of current Ebola-related activities and international attention. Above all, resources and focus currently aimed at these countries must be utilized to build up the deficit in infrastructure and healthcare systems that contributed to the extent of the Ebola outbreak.